Connexin-mediated signaling at the immunological synapse - Tittarelli, Andrés; Navarrete, Mariela; Gleisner, Maria Alejandra; Gebicke-Härter, Peter J.; Salazar-Onfray, Flavio (International journal of molecular sciences, 2020)
The immunological synapse (IS) is an intercellular communication platform, organized at the contact site of two adjacent cells, where at least one is an immune cell. Functional IS formation is fundamental for the modulation of the most relevant immune system activities, such as T cell activation by antigen presenting cells and T cell/natural killer (NK) cell-mediated target cell (infected or cancer) killing. Extensive evidence suggests that connexins, in particular connexin-43 (Cx43) hemichannels and/or gap junctions, regulate signaling events in different types of IS. Although the underlying mechanisms are not fully understood, the current evidence suggests that Cx43 channels could act as facilitators for calcium ions, cyclic adenosine monophosphate, and/or adenosine triphosphate uptake and/or release at the interface of interacting cells. These second messengers have relevant roles in the IS signaling during dendritic cell-mediated T and NK cell activation, regulatory T cell-mediated immune suppression, and cytotoxic T lymphocyte or NK cell-mediated target tumor cell killing. Additionally, as the cytoplasmic C-terminus domain of Cx43 interacts with a plethora of proteins, Cx43 may act as scaffolds for integration of various regulatory proteins at the IS, as suggested by the high number of Cx43-interacting proteins that translocate at these cell-cell interface domains. In this review, we provide an updated overview and analysis on the role and possible underlying mechanisms of Cx43 in IS signaling.
Gesehen am 05.08.2020